A Narrative Review of the Assessment of Extension and Advisory Services on an Agricultural Development Project in North - West Province, South Africa - Ijatuyi Enioluwa Jonathan; Mokone Bontle (Journal of International Agricultural and Extension Education, 2018)
The effectiveness of agriculturalextensionwork relies upon the accessibility of staffsthat are qualified, roused, conferred and receptive to the consistently evolving social, financial and political condition.This narrative seeks to highlight the role thatextension and advisory services play on a specific Agricultural Development Programme Project in North-West Province of SouthAfrica. It also exploreshow best the provincialgovernment can ensure that policies are developed and timely interventions are delivered with the needs of the farmers being considered first. Recommendations for rapid growth in the cattle and livestock industry in the provincewere also suggested
Keywords: Advisory services; Assessment; Extension services; Nguni Cattle Development Project